FAKTOR RISIKO KURANG KONSUMSI BUAH DAN SAYUR PADA ANAK USIA SEKOLAH DASAR (Studi Kasus-Kontrol pada SiswaSDN Sendangmulyo 03 Semarang Tahun 2017) - Dianissafitrah Hidayati; Suyatno Suyatno; Ronny Aruben; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Fruit and vegetable (FV) consumption in Indonesia is still low compared to other countries, particularly in school-aged children. Regular FV consumption has been associated with increased child’s immunity and reduced chronic disease risk. The aim of this study was to analyze risk factors of low FV consumption among school-aged children at Elementary School SDN Sendangmulyo 03, Semarang City. This study was analytical research with a case-control design. The samples were 43 cases and 43 control of fifth grade students selected using purposive sampling. Data were analyzed with odds ratio to know the risk factors. The risk factors of low FV consumption were low level of family welfare (OR = 2,848; 95% CI : 1,188 – 6,828), low FV availability at home (OR = 8,463; 95% CI : 3,212 – 22,297), and low parental support (OR = 6,076; 95% CI : 2,284 – 16,162). Risk factors which were not proven to influence the incidence of low FV consumption were male gender, low level of knowledge, liking FV, and mother’s education, as well as family meal frequency fewer than 3 times a week. This study suggest that the intervention designed to increase children’s FV consumption should target family members of the students in Elementary School SDN Sendangmulyo 03, Semarang City.